Modeling of low-energy charged particles passage through GAMMA-400 gamma-telescope thermal insulation and two- layer plastic scintillation detectors used as anticoincidence shield. Issue 3 (January 2016) - Chasovikov, E N; Arkhangelskaja, I V; Arkhangelskiy, A I; Kheymits, M D; Yurkin, Yu T
Abstract: The results of low-energy charged particles passage through GAMMA-400 gamma- telescope thermal insulation and two-layer plastic scintillation detectors used as anticoincidence shield are presented. An existing GEANT4 GAMMA-400 model is used. Effects of thermal insulation on charged particle passage are investigated. These results will be used to testing the effect of low-energy charged particles flux on GAMMA-400 gamma-quanta registration capabilities. Sufficiently large energy deposition in two-layer plastic anticoincidence scintillation detectors might interfere with high-energy particle registration and identification. However, GAMMA-400 detection capabilities are not affected by this, as the energy deposition in the lower layer of S3 is less than 1.5 MeV in all simulated cases. This value is less than threshold for high energy particles identification start (2.5 MeV). It makes impossible to incorrectly identify a low-energy charged particle energy deposition as backsplash from a high-energy gamma-quantum.